THE PARTICIPATION OF PROFESSIONAL PHYSICAL EDUCATION IN A CORE OF SUPPORT TO FAMILY HEALTH: PROFESSIONAL ROLE BEYOND THE IMPLEMENTATION OF PHYSICAL ACTIVITY (Fiep Bulletin - online, 2016)
With the implementation of the national policy of Health promotion public health area has become an excellent professional performance for the physical educator. An important space for this are the nuclei of support to family health (NASF), comprising multiprofessional teams service working in matrix support logic and interdisciplinarity seeking integrality of attention to health from the territorialisation of attention. The aim of this article was to present the perceptions of a professional of Physical Education about their participation, through Residência Integrada Multiprofissional em Saúde Mental Coletiva coordinated by EducaSaúde da Universidade Federal do Rio Grande do Sul, in a Núcleos de Apoio a Saúde da Família (NASF), in the municipality of Porto Alegre, Rio Grande do Sul, Brazil. Qualitative study with methodological approach of action research with participant observation, were collected the researcher's perception about their participation/intervention as a resident of EducaSaúde in the NASF - Cruzeiro, in the period from April to November 2014, the experiences were recorded in a field journal for further analysis. We observed two types of demands: an external to the NASF concerning matrix support guidelines and other internal demand, referring to action planning in the territory and the relationship with the management team/manager of the health district.In a hybrid position/resident/student worker was unable to participate in ongoing actions and intervene in the hierarchical relationship manager/team, discussing listening and reception of singularities, expansion of the clinic, interdisciplinarity and social construction of the processes of health/disease, from the notion of transcendence of the professional core of training towards the field of practices and knowledge on public health. In this sense, the NASF can be considered as spaces for professional leadership for physical education.
Keywords: Motor Activity. Health Services. Collective Health.